2016
DOI: 10.4184/asj.2016.10.6.1115
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of 1.5 Tesla Magnetic Resonance Imaging with Clinical and Intraoperative Findings for Lumbar Disc Herniation

Abstract: Study DesignA single-center prospective study.PurposeA magnetic resonance imaging (MRI) scan is undeniably the gold standard for the diagnosis of a lumbar disc prolapse. Unfortunately it shares a strong association with incidental findings. In this study, we aimed to determine the extent to which a 1.5 Tesla MRI correlates with the clinical features and intraoperative findings in cases of lumbar disc prolapse.Overview of LiteratureFew studies have correlated MRI with clinical findings, and none have extended t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…Selvaraj R. et al, 35 found that the SLRT was positive in (93.3%) in patients with disc bulge and (60%) in disc protrusion. On the other hand, Dutta S. et al, 36 confirmed that SLRT was positive in (85%), (43%), and (75%) of patients with par central, central and foraminal disc herniation, respectively.…”
Section: Fig 1: Prevalence Of Status Of Herniationmentioning
confidence: 90%
“…Selvaraj R. et al, 35 found that the SLRT was positive in (93.3%) in patients with disc bulge and (60%) in disc protrusion. On the other hand, Dutta S. et al, 36 confirmed that SLRT was positive in (85%), (43%), and (75%) of patients with par central, central and foraminal disc herniation, respectively.…”
Section: Fig 1: Prevalence Of Status Of Herniationmentioning
confidence: 90%
“…MRI films and reports of L1/L2, L2/L3, L3/L4, L4/L5 and L5/S1 disc prolapse patients were reviewed. Clinical symptoms, including pain distribution, duration of pain and intensity of pain was assessed using the Numeric Pain Rating Scale, NPRS (0-10) [13] , nerve root compression signs, and neurological signs were assessed at the dermatome level, and the response was recorded in proforma. After clinical assessment, the investigator checked the pinprick sensations using pins, needles or cotton at specific dermatomes (L1, L2, L3, L4, S1).…”
Section: Methodsmentioning
confidence: 99%
“…1.5 Tesla MRI is most frequently used in most setups, including our study. The 1.5 Tesla MRI scan is used to determine the clinical and intraoperative findings in patients with lumbar disc herniation [13] . Evidence regarding the correlation between MRI findings and clinical symptoms of disc prolapse is not sufficient [14,15] .…”
Section: How To Cite Thismentioning
confidence: 99%
“…As medidas do diâmetro do canal medular são melhor mensuradas por ressonância magnética. 3,4 Com o aumento da idade, a prevalência de EEL cresce, sendo prevalente em 9,3% na população geral e chegando a 47% em pessoas com mais de 60 anos. 5 Na faixa etária de 65 anos ou mais, a EEL é a causa mais comum de cirurgias na coluna lombar.…”
Section: Introductionunclassified